THE EFFECT OF BINJAI (Mangifera caesia) LEAVES EXTRACT GEL TO FIBROBLAST CELL NUMBER ON INCISION WOUND - Noor Hildayanti; Irham Taufiqurrahman; Renie Kumala Dewi (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: The ethanol extract of binjai leaves contains bioactive compounds that are saponin, tannin, triterpenoid, steroid, alkaloid and flavonoid which potentially as an anti-inflammation, anti-bacterial, and antioxidant. It can fasten and control the process of scar healing. The binjai leaves extract was made into gel preparation. The binjai leaves extract gel can affect fibroblast cell number during the proliferation phase. Purpose: To analyze the effect of binjai (Mangifera caesia) leaves extract gel to the fibroblast cell number on male wistar rats (Rattus norvegicus) incision wound.  Methods: This research design was a true laboratory experimental research with post-test only with control group design which used 24 male wistar rats and divided into 4 groups: the negative control group that was given the placebo gel and the treatment group that was given the binjai leaves extract gel with 5%, 10%, and 15% concentrations. Results: The result of Two-way ANOVA statistic test shows that there is a meaningful difference in the treatment group on the 7th day (p=0,000) and on the 14th day (p=0,000). The Post-Hoc Bonferroni test for fibroblast cell number on the 7th and 14th day shows that there is a meaningful difference (p<0,05) between the negative control group and the treatment group. Conclusion: Binjai leaves extract gel have an effect to the fibroblast cell number on male wistar rats incision wound with the most effective concentration of 15%. Keywords: Binjai leaves extract gel, Fibroblast cell number,  Flavonoid, Incision wound healing